Docking against Lung cancer protein and Drug-likeliness of Bioactive Compounds from Phymatosorus scolopendria (Burm.F.) Pic. Serm. (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Phymatosorus scolopendria (Burm.F.) Pic. Serm. is a medicinally important fern which is used traditionally by various people all over the World. The aim of this research focuses on the docking against lung cancer protein (2ITO) with bioactive compounds of Phymatosorus scolopendria (Burm.F.) Pic. Serm. which is obtained by using Gas Chromatography Mass Spectroscopy. The same compounds were analysed using Lipinski’s rule of five for its pharmacological prediction. The bioactive compounds were further referred for ADMET property to find its pharmacokinetic potency and prediction towards its potential as drug in future. Among the four compounds docked with the Lung cancer protein (2ITO) 4-Nitrophenyl laurate shows high docking score followed by Hexadecanoic acid, 4 Nitrophenyl ester and Myristic acid Vinyl ester. Out of four compounds studied three compounds satisfied the drug-likeliness based on Lipinski’s rule of five. The present work suggests the bioactive compounds of Phymatosorus scolopendria (Burm.F.) Pic. Serm. for further in vitro and in vivo studies for its anticancer benefits especially related to lung cancer.